The effect of particle size on the physical and drug-release behaviour of chloramphenicol-loaded mini-tablets for ocular use - Mohmad Sabere, Awis Sukarni; Barker, Susan A.; Craig, Duncan (2014)
Ocular drug delivery is challenging because of the inherent difficulty of accessing the target sites, especially those in the posterior segment of the eye. The natural defence mechanisms, such as the constant turnover of the tear film on the surface of the eye and the blink reflex, reduce the amount of drug that is therapeutically available after surface administration. Eye drops have continued to be used as the main vehicle for ocular therapy due to their perceived patient acceptance, despite the disadvantages of fast removal and low overall drug bioavailability. Ocular mini-tablets are a potential method of improving the retention time at the site of administration and hence promoting the efficiency of drug therapy. Mini-tablets have a diameter of around 2 mm and a total weight of circa 10 mg. They can be inserted into the ocular pocket at the front of the eye, where they will hydrate and release the drug into the surface ocular fluid. Formulation and production of mini-tablets is similar to conventionally-sized tablets, but there are specific issues related to the control of the particle size distribution of the component powders that are much more significant for mini-tablets than larger tablets.